Consanguinity and Positive Family History of Inflammatory Bowel Diseases in Children: A Multicenter Case–Control Study - Hasosah, Mohammed (Journal of Child Science, 2022)
Inflammatory bowel diseases (IBD), which comprise Crohn's disease (CD) and ulcerative colitis (UC), are rising trend in Saudi population. We aim to examine the association between consanguinity and family history and the risk of childhood IBD in Saudi children. A multicenter case–control study conducted in three tertiary hospitals in Jeddah and Riyadh, Saudi Arabia, during periods 2009 to 2021. Data about demographics, consanguinity, family history of IBD, and type of IBD were collected using a structured questionnaire. The same questionnaire was applied in matched case–control. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression analysis that was performed to compare both groups. The study population included 335 children: 167 IBD patients (49.9%) and 168 controls (50.1%). Of these IBD, 93 patients (56%) were CD and 74 patients (44%) were UC. Most of participants were females (72.1%) and their age more than 10 years (51.5%). There was first-degree consanguinity in 66 IBD patients (49.6%). No significant difference in first-degree consanguinity between cases and controls was noted (49.6% in cases vs. 50.4% in controls; OR = 1.02; 95% CI = 0.66–1.57). The consanguinity showed a more significant association with CD than UC (p < 0.05). Family history of IBD (father, siblings, and grandparents) as risk factors for IBD was identified: paternal history of IBD (OR = 0.25, 95% CI = 0.08–0.76), siblings' history of IBD (OR = 2.16, 95% CI = 1.92–2.43), and grandparent's history of IBD (OR = 0.22, 95% CI = 0.07–0.65). Family history of IBD showed a more significant association with CD than UC (p < 0.05). Consanguinity is strongly associated with IBD with more significant association with CD than UC and may possibly explain IBD rise in Saudi Arabia. The greatest risk of family history of IBD is in first-degree relatives, especially in siblings' rather than parents and grandparents.
Keywords: inflammatory bowel diseases; consanguinity; family history